2020
DOI: 10.1093/jn/nxaa249
|View full text |Cite
|
Sign up to set email alerts
|

Brain α-Tocopherol Concentration and Stereoisomer Profile Alter Hippocampal Gene Expression in Weanling Mice

Abstract: Background Alpha-tocopherol (αT), the bioactive constituent of vitamin E, is essential for fertility and neurological development. Synthetic αT (8 stereoisomers; all rac-αT) is added to infant formula at higher concentrations than natural αT (RRR-αT only) to adjust for bio-potency differences, but its effects on brain development are poorly understood. Objectives The objective was to determine the impact of bio-potency–adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…We believe these finding to be important for several reasons beyond the well-documented differences in vitamin E activity between RRR -αT and S-αT ( 5 ). αT has increasingly been found to influence gene expression ( 30 35 ), and more recently, evidence is accumulating that S-αT stereoisomers and RRR -αT have differential impacts on gene expression in the brain ( 20 , 36 , 37 ). In addition, improved maternal αT status appears to positively influence fetal growth ( 19 , 38 42 ), but recently cord plasma αT concentration was reported to be negatively related to neonate 5-min Apgar (physician ratings of the newborn infant's appearance, pulse, grimace, activity, respiration) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe these finding to be important for several reasons beyond the well-documented differences in vitamin E activity between RRR -αT and S-αT ( 5 ). αT has increasingly been found to influence gene expression ( 30 35 ), and more recently, evidence is accumulating that S-αT stereoisomers and RRR -αT have differential impacts on gene expression in the brain ( 20 , 36 , 37 ). In addition, improved maternal αT status appears to positively influence fetal growth ( 19 , 38 42 ), but recently cord plasma αT concentration was reported to be negatively related to neonate 5-min Apgar (physician ratings of the newborn infant's appearance, pulse, grimace, activity, respiration) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, the of this study highlight the effects of the consumption of ultra-processed foods during lactation on both mother and infant as maternal serum α-tocopherol levels are associated with low circulating levels in the child, even without maternal deficient serum levels (20) . Moreover, a reduced supply of vitamin E in the breast milk or maternal concentration can cause greater oxidative damage due to reduced antioxidant protection in the infant provided by vitamin E (42) and gene expression genes involved in transcription regulation and synapse formation in the hippocampus are very sensitive to subtle changes in α-tocopherol concentration (43) . This in turn makes the infant, particularly premature babies, more susceptible to the development of clinical complications related to VED, such as hemolytic anaemia, retrolental fibroplasia, intracranial haemorrhage and bronchopulmonary dysplasia (42) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, time-course bioaccumulation of natural vs. synthetic α-Toc in tissues of young marginally VE-deficient mice showed that bioaccumulation of α-Toc over time varied substantially depending on α-Toc source and tissue type; Natural α-Toc showed higher accumulation levels in heart, lungs, kidney, brain and adipose tissue than synthetic one 43) . Besides, in mice, natural and synthetic VEs modulate transcription of different genes, suggesting in vivo effects are related to the fine structure of the molecules 44,45) . It is claimed that although RRR-α-Toc is the predominant stereoisomer in human milk, synthetic (all-rac) -α-Toc is commonly used in infant formulas 46) .…”
Section: Synthesismentioning
confidence: 99%